"A different world" exploring and understanding the climate of a recently re-rolled sexual offender prison. Issue 2 (4th May 2017) - Blagden, Nicholas; Perrin, Christian; Smith, Sam; Gleeson, Faye; Gillies, Laura
ABSTRACT: Understanding how sexual offenders experience prison and its environment is important because such experiences can impact on rehabilitation outcomes. The purpose of this research investigation was to explore the rehabilitative and therapeutic climate of a recently re-rolled sexual offender prison. The research took a mixed methods approach and consisted of quantitative and qualitative phases. There were differences between prisoners and staff on their perception of the prison climate and for prisoner and staff relationships. The qualitative results helped to explain the quantitative findings and added a more nuanced understanding of the experience of the prison, the nature of prisoner and staff relationships and the opportunities for personal growth within the prison. The study has important implications for prisons that co-locate sexual offenders and want to provide an environment conducive to rehabilitation.